Impact of dual energy characterization of urinary calculus on management. Issue 5 (28th July 2016) - Habashy, David; Xia, Ryan; Ridley, William; Chan, Lewis; Ridley, Lloyd
Abstract: Introduction: Dual energy CT (DECT) is a recent technique that is increasingly being used to differentiate between calcium and uric acid urinary tract calculi. The aim of this study is to determine if urinary calculi composition analysis determined by DECT scanning results in a change of patient management. Method: All patients presenting with symptoms of renal colic, who had not previously undergone DECT scanning underwent DECT KUB. DECT data of all patients between September 2013 and July 2015 were reviewed. Urinary calculi composition based on dual energy characterization was cross‐matched with patient management and outcome. Results: A total of 585 DECT KUB were performed. 393/585 (67%) DECT scans revealed urinary tract calculi. After excluding those with isolated bladder or small asymptomatic renal stones, 303 patients were found to have symptomatic stone(s) as an explanation for their presentation. Of these 303 patients, there were 273 (90.1%) calcium calculi, 19 (6.3%) uric acid calculi and 11 (3.4%) mixed calculi. Of those with uric acid calculi, 15 were commenced on dissolution therapy. Twelve of those commenced on dissolution therapy had a successful outcome, avoiding need for surgical intervention (lithotripsy or stone retrieval). Three patients failed dissolution therapy and required operative intervention for definitive management of the stone. Conclusion: Predicting urinary tract calculi composition by DECT plays an important role in identifying patients who may be managed with dissolution therapy. Identification of uric acid stone composition altered management in 15 of 303 (5.0%) patients, and was successful in 12, thereby avoiding surgery and its attendant risks.